2009
DOI: 10.1002/adsc.200800703
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Palladium‐Catalyzed Oxidative Csp2Csp3 Cross‐Coupling of Arylzinc and Alkylindium Reagents through Double Transmetallation

Abstract: Using desyl chloride (2-chloro-1,2-diphen-A C H T U N G T R E N N U N G ylethanone) as the oxidant, the palladium-catalyzed reaction of arylzinc with alkylindium reagents occurred smoothly in a highly selective manner to afford the products in 57-90% yields. Preliminary kinetic data indicated that alkylindium reagents were highly favored for transmetallation with the alkoxypalladium moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…Notably,the yield and product distribution remained essentially unchanged when the amount of BINAP was reduced from 10 mol %to5or3mol %(entries 8and 9). DMA and NMP were identified as optimal solvents (entries 10 and 11), and ultimately the yield was improved to 82 %byfine-tuning the reaction temperature,the amounts of BQ and TBAF used, and the concentration (entries [12][13][14]. Replacing BINAP with PPh 3 (3 or 6mol %) under otherwise unchanged conditions resulted in al ow yield of 3aa and the formation of al arge quantities of 4aa (entries 15 and 16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably,the yield and product distribution remained essentially unchanged when the amount of BINAP was reduced from 10 mol %to5or3mol %(entries 8and 9). DMA and NMP were identified as optimal solvents (entries 10 and 11), and ultimately the yield was improved to 82 %byfine-tuning the reaction temperature,the amounts of BQ and TBAF used, and the concentration (entries [12][13][14]. Replacing BINAP with PPh 3 (3 or 6mol %) under otherwise unchanged conditions resulted in al ow yield of 3aa and the formation of al arge quantities of 4aa (entries 15 and 16).…”
Section: Methodsmentioning
confidence: 99%
“…[13] Significantly,p alladium-catalyzed cross-couplings of alkyl zinc reagents with alkynylstannanes were achieved by the Lei group,a nd the method was successfully extended to the reaction of aryl zinc and alkyl indium reagents ( Figure 2b). [14] TheCahiez group reported iron-and manganese-catalyzed selective couplings of two different organozinc or organomagnesium reagents (Figure 2c,d). [15] Furthermore,H irao and co-workers disclosed as eries of…”
mentioning
confidence: 99%
“…Palladium catalysis has proved useful in this context. Oxidative C(sp 2 )-C(sp 3 ) coupling between arylzinc and alkylindium reagents occurs with desyl chloride as oxidant in the presence of PdCl 2 (MeCN) 2 (5 mol%) and DPEPhos (174) (5 mol%) at 60 • C in THF [166] (Scheme 4.45). Mechanistically, it is suggested that the low-valent Pd(0) species undergoes oxidative addition with desyl chloride to produce an O-bonded Pd enolate.…”
Section: Recent Mechanistic Insightsmentioning
confidence: 99%
“…This complex does not undergo reductive elimination and only isomerizes to cis-374 slowly, which in addition allows for other side reactions, such as a second transmetallation to provide 376, to take place. As illustrated with the formation of 379, oxidative coupling between primary alkylzincs and alkynylstannanes occurs under similar conditions as those discussed above for the reaction between arylzincs and alkylindium reagents [165,166]. Desyl chloride is used as oxidant in the presence of Pd(dba) 2 (2.5 mol%) at 60 • C in THF (Scheme 4.87) [273].…”
Section: Cross-coupling With C(sp 3 )-Electrophilesmentioning
confidence: 99%
“…Recently, our research group has reported that a-haloketones can be employed as an oxidant in both oxidative coupling reactions and oxidative carbonylation, thus indicating that the transmetalations of both Pd À X and palladiumenolate bonds (generated from the oxidative addition of ahaloketones to Pd 0 ) with nucleophiles like arylzinc reagents and arylboronic acids are very facile. [11] This finding indicates that a-haloketones are poor coupling partners with nucleophiles in the presence of transition-metal catalysts. However, the functionalization of a-haloketones is important.…”
mentioning
confidence: 97%